The uncertainty of debt service payments and economic growth of HIPCs: Is there a case for debt relief? - Geske Dijkstra; Niels Hermes (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2001)
This paper investigates whether, and to what extent, the uncertainty with respect to the annual debt service payments may adversely affect economic growth of the group of highly indebted poor countries (HIPCs). We find supportive evidence for this hypothesis. Based on these results, we conclude that debt relief may contribute to regaining growth by reducing uncertainty with respect to the debt service payments, which in turn may increase the effectiveness of government policies and consequently provide the private sector with positive signals about the future profitability of their investment.
Keywords: F34; E6; O11; 330; debt relief; uncertainty; debt service; HIPC; Auslandsschuldendienst; Schuldenerlass; Risiko; Wirtschaftswachstum; Entwicklungsländer